Impact of COVID-19 pandemic on dermatology practices: Results of a web-based, global survey - Shashank Bhargava, MD; Charles McKeever, MD; George Kroumpouzos, MD, PhD, FAAD (Wolters Kluwer, 2021)
The spectrum and magnitude of changes in dermatology practice induced by the COVID-19 pandemic have not been adequately studied. Objective: This study aimed to assess the immediate and long-term effects of the pandemic on dermatology practice on a large scale, including the clinical activity of participants, frequency and types of procedures used, and teledermatology (TD) use. Methods: This web-based, global survey included 733 dermatologists. The primary outcomes are percentages of respondents providing in-person consultations, hospital service, and TD and performing procedures. Factors in logistic regression models that may influence the odds ratio (OR) for TD use during pandemic and for future use also were analyzed. Results: The percentages of respondents providing in-person consultations (46.6% vs. 100% before the pandemic) and hospital service (27% vs. 52.8% before the pandemic) as well as performing procedures (25.6% vs. 100% before the pandemic) decreased, whereas practicing TD increased three-fold (75.2% vs. 26.1% before the pandemic) during the pandemic (p < .001 for each). Practice location was associated with TD use during the pandemic and with its expected use in the future (p < .001 for both), with North American respondents indicating the highest use. TD use during the pandemic showed a positive correlation with TD use before the pandemic, performing procedures and, more specifically, with biopsies of suspicious pigmented lesions during the pandemic (p < .001 for each). TD use before the pandemic was the most powerful predictor of TD use during the pandemic (OR: 16.47; 95% confidence interval, 7.12-38.06). More than two third of participants (68.6%) expect to use TD in the future. The factor with the largest increase in OR on the expectation of future TD use was >1000 COVID-19 cases in the country (OR: 3.80; 95% confidence interval, 2.33-6.21). Conclusion: This survey indicates a profound immediate effect of the pandemic on dermatology practice. The pandemic appears to have substantially contributed to an increased use of TD in the long run.